Reestructuración técnico administrativa para la empresa Calderón Franco y Cia LTDA (2020)
This paper presents the proposal for the realization of a technical-administrative restructuring for the company Calderón Franco y Cía, which begins with an internal and external analysis of the same in order to reach a diagnosis, using tools such as the PESTAL, which allowed to identify the opportunities and threats of the company in the city and the country; the identification of strengths and weaknesses was carried out with the help of the business diagnosis offered by the Chamber of Commerce of Bogotá, the collection of information gave way to the realization of the DOFA matrix.